Anterior Decompression and Anterior Instrumentation of Tuberculosis of Cervicothoracic Spine by Cervicomanubrial Approach - Anant Kumar Garg; Parag Garg; S. Ayan; Vikas Keshari; Debi Kundu; Gautam Bhattacharya (Al Ameen Medical College, 2012)
Background: Evaluation of result of anterior cervical approach with manubriotomy and anterior instrumentation in tuberculosis of cervicothoracic spine in terms of the neurological recovery, reconstruction of spine and prevention of deformity along with relief of pain. Materials and Methods: All five patients with cervicothoracic caries spine had surgery through anterior cervical approach with manubriotomy in our hospital and underwent excision of the involved vertebrae and intervertebral discs followed by anterior spinal reconstruction with titanium spacer cage filled with cancellous iliac crest bone graft and Orion plate with locking screw. Antitubercular drugs were administered for 12 months. The follow-up period ranged from 12 to 36 months. Results: Analysis of result was done on the basis of clinical and radiological criteria. Clinical assessment based on Frankel grade and modified JOA score showed significant improvement from preoperative findings. Radiological assessment showed osteointegration, no spinal instability and no progression of the deformity. The pain control, based on visual analog scale changed from a pre-operative average of 7.5 to 2 at the last follow-up thereby indicating significant improvement and all patients returned to preoperative functional status. One patient had transient hoarseness of voice. No other complication had been encountered in the immediate post operative and during the follow-up period. Conclusions: Our study showed that anterior cervical approach with manubriotomy and anterior insertion of titanium cage, filled with autogenous bone graft, secured with locking plate instrumentation has a successful role in the eradication of infection, neurological recovery, segmental spinal reconstruction and it also reduces surgical time, blood loss, and surgical complications and approach related comorbidity in follow up period. Level of Evidence- Level 4, Case series